Sudden outbreak of mealybug and armoured scale causing severe damage to economic crops in Bangladesh (The Journal of Plant Protection Sciences, 2021)
Recently attack of different vegetable crops viz., eggplant, lady's finger, papaya, basil etc. by citrus mealybug,  Planococcus citri (Risso) (Homoptera: Pseudococcidae) has been noticed in Bangladesh. It is mainly a pest of citrus and  coffee crops but now it has become polyphagous in nature. Based on laboratory studies on immature and mature fruits of  lady's finger; the total period of all four nymphal stages lasted for 32.6 ± 4.17 days at an average room temperature of 28  ± 2ºC and 70-75% RH during September, 2009. Male mealybug has a short life span of 3.0 ± 0.21 days. Females live for  nearly 80.7 ± 10.43 days with an oviposition period of approximately 21 days. This mealybug is capable of active  movement throughout its adult life. The stripped mealybug, Ferrisia virgata (Cockerell) was found to infest the leaves of  different ornamental plants in Rajshahi and Dhaka, Bangladesh. It is a polyphagous pest damaging coffee, sweet potato,  jute, groundnut, tomato, citrus, cotton, guava etc. causing enormous damage to them. The female lays about 300-400  eggs which hatch in few hours. The life cycle is completed in about 40 days. The small and big black ants tend F. virgata and they keep other insects including hymenopteran parasites away from the mealybug. The cottony cushion scale,  Icerya purchasi Mask. (Homoptera: Margarodidae) is a soft-bodied mealybug infesting guava leaves all over  Bangladesh. It is reddish-brown and lays up to 600-700 eggs during her lifetime. The life cycle is completed within 46- 240 days depending on different environmental conditions. The females develop parthenogenetically. It is a sucking pest  and mainly feeds on citrus. Its secondary hosts include fig, apple, almond, guava etc. Due to severe infestation,  premature falling of leaves occurs. The ber or plum scale, Aonidia ziziphi Rah. was recorded from Rajshahi, Bangladesh  as a serious pest of ber or plum plant damaging the leaves and immature fruits during December-January, 2007. The  female reproduces parthenogenetically. Due to severe attack of mealybug, the pericarp of immature fruit is damaged to  some extent and it becomes unfit for human consumption and market value is greatly reduced.
Keywords: Mealybug; Planococcus citri; armoured scale; Aonidia ziziphi; life cycle; maphometric studies